Effect of Green Tea Extract in Conjunction with Exercise Prices of Training on Anaerobic Performances in College Students’ Outcomes - Mao, Qiping; Thanaphonganan, Napatsawan (Journal of Ecohumanism, 2024)
To evaluate the effects of various interventions on anaerobic power, fatigue index, and overall performance in college students. Participants were 30 college students aged 18-22 years from Sichuan Vocational College of Health. Their height, weight, and anaerobic capacity were measured using the running-based anaerobic sprint test (RAST). We divided the students into three groups of 10 participants each, consisting of 3 males and 7 females, based on their RAST test scores. Group 1 received a placebo (500 mg) combined with 4 weeks of athletic training; Group 2 received a single dose of 500 mg of green tea extract with exercise; and Group 3 received 500 mg of green tea extract combined with 4 weeks of athletic training. Before-and-after-experimental data research designs were compared using a t-test analysis, while differences between groups were assessed. The results showed that statistically significant were not differences in anaerobic capacity for Group 1, while Group 2 displayed significant improvements in anaerobic capacity and mean power among female students (p<.05). Group 3: students’ exercise training on anaerobic power, fatigue index, and mean power variables are differences, significant for both male and female students (p<.05). Confirmation of the effect of green tea extract in conjunction with exercise prices of training on anaerobic performance in college students’ outcomes between each paired-group using one-way ANOVA, the results revealed that the four variables are differences, significant in anaerobic power, average power, and fatigue index across the groups, and Group 3 indicating the most notable improvements. Suggestions that, combining green tea extract with prolonged athletic training significantly improves anaerobic capacity, particularly in female participants. These results highlight the potential benefits of green tea extract in enhancing athletic performance, warranting further research to explore its long-term effects and optimize exercise interventions.